The Influence of Nutritional Status and Age at Menarche on the Incidence of Dysmenorrhea among Female Adolescents at the Senior High School Level - Hidayah, Alula; Mandali, Rumi; Rahmah, Zulaikha Nisa (Media of Health Research, 2025)
This study aims to analyze the influence of nutritional status and age of menarche on the incidence of dysmenorrhea in female adolescents at the high school level. Dysmenorrhea is a common complaint of menstrual pain experienced by adolescents, which can affect their quality of life and activities. Factors such as nutritional status and age of menarche are believed to play an important role in determining the intensity and frequency of dysmenorrhea. This study uses an analytical observational design with a cross-sectional approach, involving 150 female adolescents from several high schools in East Java. Nutritional status data were collected through body mass index (BMI) measurements, while the age of menarche was obtained through a questionnaire. The incidence of dysmenorrhea was measured based on the adolescents' subjective reports of the intensity of menstrual pain experienced. Data analysis was performed using chi-square tests and logistic regression to determine significant relationships between these variables. The results of the study show that poor nutritional status and younger age of menarche have a significant influence on the increased incidence of dysmenorrhea in female adolescents. These findings can provide important information for healthcare professionals and educators to offer appropriate interventions in reducing the impact of dysmenorrhea on female adolescents.